THE WRONG QUESTION! PLEASE CHANGE THE SUBJECT! - Hollinger, David A. (Fides et historia, 2011)
The author reflects on the role of historians' religious beliefs in the practice of religious history. His article responds to the essays "Mormon History Inside Out" by Richard Lyman Bushman, "Historians’ Metaphysical Beliefs and the Writing of Confessional Histories" by Brad S. Gregory, and "Coming to Terms as a Christian Historian with F. H. Bradley" by Mark A. Noll. According to the author, historians should not preface their works with statements of their own personal beliefs, lest these disclosures make readers skeptical of an otherwise reliable and informative piece of scholarship. It is suggested that an emphasis on supernatural causation will drive historians with secular worldviews away from the field.